2021
DOI: 10.3389/fchem.2021.691565
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions Between Antibiotic Resistance Genes and Heavy Metal Pollution Under Co-Selective Pressure Influenced the Bio-Enzyme Activity

Abstract: The spread of antibiotic resistance genes (ARGs) has brought potential risks to public health. However, the interactions between heavy metals and ARGs, as well as their potential effect on bio-enzyme activity under the pressure of co-selectivity in soil still remain poorly understood. In this work, the distribution characteristics and the co-selective relationship of 28 ARGs and eight heavy metals in soil in a dairy farm were visualized via the geographic information system (GIS) technique. Eight kinds of heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Bacteria exposed to arsenic-contaminated groundwater may induce or select bacterial adaptations to one or more antibiotics through co-selection of resistance. This is in agreement with previous studies that organisms isolated from extreme environmental conditions such as industrial or agricultural wastewater have shown arsenic-mediated antibiotic resistance in vitro [ 15 , 42 , 53 ]. In a related study, 6 h arsenic exposure [As(III) of 0.2–1 mg/L] in drinking water increased bacterial resistance to cephalosporin, tetracycline, and erythromycin as well as increased the relative abundance of antibiotic resistance genes in a bacterial community [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Bacteria exposed to arsenic-contaminated groundwater may induce or select bacterial adaptations to one or more antibiotics through co-selection of resistance. This is in agreement with previous studies that organisms isolated from extreme environmental conditions such as industrial or agricultural wastewater have shown arsenic-mediated antibiotic resistance in vitro [ 15 , 42 , 53 ]. In a related study, 6 h arsenic exposure [As(III) of 0.2–1 mg/L] in drinking water increased bacterial resistance to cephalosporin, tetracycline, and erythromycin as well as increased the relative abundance of antibiotic resistance genes in a bacterial community [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Heavy metal pollution is one of the most significant sources of environmental contamination (Roane and Kellogg 1996 ) and represents a long-term selection pressure on microbial communities (Stepanauskas et al 2005 ). Moreover, toxic compounds, including heavy metals, can support and co-select antibiotic resistance through different mechanisms, such as co-resistance, cross-resistance, and co-regulation (Baker-Austin et al 2006 ; Gupta et al 2022 ; Vats et al 2022 ), which may lead to greater diversity and abundance of antibiotic resistance genes in the microbial communities (Qi et al 2021 ). The genes related to toxic compounds detected in the MAGs included all categories previously found in the metagenomic dataset (Banchi et al 2021 ), which may indicate a higher prevalence of these features compared to antibiotic resistance ones.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increased use of antibiotics in agriculture, microorganisms are developing resistance either by natural mutation or by transfer of resistant genes between themselves. Heavy metals along with antibiotics create a selective pressure that help microorganisms to adapt for better survival in multiple stress conditions [25]. Thus, resistance to both heavy metals and antibiotics make P. aeruginosa HMT 7 more ecologically favourable.…”
Section: Discussionmentioning
confidence: 99%